3D printing of non-assembly spatial mechanisms - Teo, Yong Yun (Nanyang Technological University, 2024)
This project focuses on the design and fabrication of non-assembly spatial mechanisms using FDM 3D printing. Revolute Joints, Universal Joints and Spherical Joints were designed to be non-assembly and printed. Iteration was conducted to obtain the necessary clearances to achieve satisfactory motion of the three types of joints. The information collected was used to facilitate the design of two non-assembly spatial mechanism, namely the Bennet Linkage and the Crank Slider. The Bennet Linkage utilised the findings from the Revolute Joints, while the data obtained from all three joints were used for the creation of the Crank Slider. Motorisation was also done on both the Bennet Linkage and Crank Slider mechanisms to study their movement under controlled actuation. Additionally, a modular based was developed and produced to securely mount the mechanisms during rotation. Through the meticulous testing done throughout this project, crucial dimensions and clearances for non-assembly joints and spatial mechanisms were obtained, providing valuable insights for future development in this field. This project demonstrated the potential of FDM 3D printing in creating these mechanism and lays the foundation for future exploration of such mechanisms in various engineering applications.